An investigation of Joule-heating flow in a cubic cavity using finite element method - T.T. Duong; H.Tanaka; N.Tsuzuki; H.Kikura; H.Kawai (Nuclear Science and Technology, 2013)
The effect of cooling condition of electrode side wall on the flow behavior in a cubic cavity with volumetric Joule-heating is studied numerically and experimentally.Chaotic unstable flow occurs in the cavity which is volumetrically heated, mainly by electric current as Joule-heating by placing electrode on opposing side wall, meanwhiletop surface is cooled by constant temperature. Two carbon plates are placed on opposing side wall and connected a constant AC voltage in order to generate an internal heat source. The chaotic flow behavior under Joule-heating condition is known as difficult to stabilize and simulate by computational codes. Thus, a numerical model using Finite Element Method, GSMAC-FEM, which applies coupled solution of temperature field, flow field and magnetic field,is utilized to simulate the flow behavior of this experiment and compared with experimental results. In order to confirm numerical results, velocity and temperature profile is measured at center of cavity. The temperature comparison is well agreed between numerical analysis and experimental data. For flow measurement, two-dimensional velocity distribution in middle part between two electrodes is visualized by Particle Image Velocimetry (PIV). Moreover, one-dimensional spatial-temporal velocity profiles are observed by Ultrasound Velocity Profiler (UVP). These methods have some advantages such as non-intrusive is used to qualitatively compare with numerical results. As results, a chaotic flow is successfully simulated by FEM method. The vortices with low velocity are occurred in the half part of cavity and a strong downward flow near electrode plate is observed.